Hubungan Antara Pengelolaan Perpustakaan dengan Motivasi Belajar Siswa Kelas V Sekolah Dasar - Muh Idris Jafar; adnan,K Adnan,K; Asriadi Asriadi; Nur Apriani Kasti (Universtas Negeri Makassar, 2022)
The problem in this research is the ineffectiveness of library management so that students are less motivated in learning. This study is a quantitative study with a correlation design that aims to determine whether there is a relationship between library management and learning motivation of fifth grade students at SD Inpres 12/79 Lonrae. The results showed that there was a significant relationship between library management and learning motivation of fifth grade students at SD Inpres 12/79 Lonrae with t count (4.1136) greater (>) t table value (1.66660) which means H0 is rejected and H1 is accepted. Based on the analysis of the data above, it can be concluded that library management will have an impact on the mindset of students in learning so that it will affect their learning motivation in the classroom. So, the better the management of the library, it will increase student learning motivation. From these conclusions, the impact of this research is known that good library management will increase students' learning motivation